Hawthorn Lace Bug, Corythucha cydoniae (Fitch) (Insecta: Hemiptera: Tingidae) - Frank W. Mead (EDIS, 2002)
The hawthorn lace bug, Corythucha cydoniae (Fitch), selectively attacks a variety of woody, rosaceous plants and can cause severe leaf damage. The principal Florida host is firethorn, Pyracantha coccinea Roemer. This document is EENY-080, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: May 1999.